Liquid biopsy markers for stroke diagnosis. (2nd August 2020) - Wijerathne, Harshani; Witek, Malgorzata A.; Baird, Alison E.; Soper, Steven A.
ABSTRACT: Introduction: There is a short time window (4.5 h) for the effective treatment of acute ischemic stroke (AIS), which uses recombinant tissue plasminogen activator (rt-PA). Unfortunately, this short therapeutic timeframe is a contributing factor to the relatively small number of patients (~7%) that receive rt-PA. While neuroimaging is the major diagnostic for AIS, more timely decisions could be made using a molecular diagnostic. Areas covered: In this review, we survey neuroimaging techniques used to diagnose stroke and their limitations. We also highlight the potential of various molecular/cellular biomarkers, especially peripheral blood-based ( i.e . liquid biopsy) biomarkers, for diagnosing stroke to allow for precision decisions on managing stroke in a timely manner. Both protein and nucleic acid molecular biomarkers are reviewed. In particular, mRNA markers are discussed for AIS and hemorrhagic stroke diagnosis sourced from both cells and extracellular vesicles. Expert opinion: While there are a plethora of molecular markers for stroke diagnosis that have been reported, they have yet to be FDA-cleared. Possible reasons include the inability for these markers to appear in sufficient quantities for highly sensitive clinical decisions within the rt-PA therapeutic time